UTILIZATION OF INFORMATION TECHNOLOGY IN PREVENTION OF DEPRESSION IN OLDER ADULTS - Anung Ahadi Pradana; Junaiti Sahar; Henny Permatasari (Jurnal Kesehatan, 2021)
Depression is a problem that often occurs in the older adults population. The use of technology in the implementation of health services has succeeded in increasing the effectiveness and quality of providing health services to patients. Several mobile apps that have been available have the potential to improve services for people with depression. The purpose of this study was to determine the use of information technology in preventing depression in older adults. This study uses a simple literature study method based on a specific theme from several databases including the Cumulative Index to Nursing and Allied Health Literature (CINAHL), ProQuest, and SAGE between 2014 and 2020. 27 journal articles that met the inclusion criteria passed the screening process using the PRISMA diagram. Research showed positive results in the use of technology for depressive conditions experienced by older adults. The importance of developing health applications in order to keep up with the conditions needs to be the attention of health workers. Easy, inexpensive, and attractive health applications can increase public curiosity and participation in the health sector.